The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/1941738115607208
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar Collateral Ligament Reconstruction

Abstract: Context:Ulnar collateral ligament (UCL) injuries lead to pain and loss of performance in the thrower’s elbow. Ulnar collateral ligament reconstruction (UCLR) is a reliable treatment option for the symptomatic, deficient UCL. Injury to the UCL usually occurs because of chronic accumulation of microtrauma, although acute ruptures occur and an acute-on-chronic presentation is also common.Evidence Acquisition:Computerized databases, references from pertinent articles, and research institutions were searched for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
56
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 73 publications
(126 reference statements)
0
56
1
5
Order By: Relevance
“…Studies have shown that there is no advantage conferred by the use of a single or double-bundle reconstruction [15]. Classically, the palmaris longus is used, but was nonexistent in this patient [16]. The use of toe extensors has been described for collateral ligaments of the elbow but accounts for less than 2% of all autograft used according to a recent review of the literature and meta-analysis of 619 patients [1719].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that there is no advantage conferred by the use of a single or double-bundle reconstruction [15]. Classically, the palmaris longus is used, but was nonexistent in this patient [16]. The use of toe extensors has been described for collateral ligaments of the elbow but accounts for less than 2% of all autograft used according to a recent review of the literature and meta-analysis of 619 patients [1719].…”
Section: Discussionmentioning
confidence: 99%
“…16,18,22,2729 With the advent of UCL reconstruction, the volume of procedures has increased, as reported in the peer-reviewed literature and public media. 3,9,25,26 However, in 2 reports by Camp et al, 4,5 the incidence of UCL reconstructions may be decreasing among professional baseball players but increasing in younger, minor league players. Hurwit et al 16 surveyed 159 members of the American Shoulder and Elbow Surgeons and found that professional athletes and those with complete tears were indicated for surgery by consensus regardless of the tear location; opinion was more divided on how to treat partial tears or nonprofessionals.…”
mentioning
confidence: 99%
“…Injuries to the medial ulnar collateral ligament (UCL) of the elbow are increasingly diagnosed and treated, particularly among baseball players and other overhead-throwing athletes. 3,7,9,10,15,21 While surgical management has translated to improved functional and patient-reported outcomes, identifying which patients will most likely benefit from UCL reconstruction remains elusive. 16,18,22,2729 With the advent of UCL reconstruction, the volume of procedures has increased, as reported in the peer-reviewed literature and public media.…”
mentioning
confidence: 99%
“…7 Each of these techniques involves drilling either tunnels or a socket in the medial epicondyle. 2,3,9,24…”
mentioning
confidence: 99%